Seasonal and Regional Differences in Lighting Conditions and their Influence on Melatonin Secretion - Błażejczyk, Krzysztof; Morita, Takeshi; Ueno-Towatari, Tomoko; Błażejczyk, Anna; Wieczorek, Joanna (Quaestiones Geographicae, 2014)
The paper presents essential results of multidisciplinary research dealing with differences in lighting conditions (natural and/or artificial) and their possible influence on melatonin secretion studied in Fukuoka (Japan) and in Warszawa (Poland). Several characteristics of lighting were considered (intensity of global 0.4-3.0 μm, visible 0.4 0.76 μm solar radiation, illuminance (lux), peak irradiance (μW∙cm−2∙nm−1), Color Corresponded Temperature (CCT, K) and peak wave length (nm)). Diurnal cycle of melatonin secretion was examined at volunteers (Poland - 15, Japan - 18), young male and female (21-33 years). Saliva samples were collected at 3h intervals, beginning at 10:00h on Thursday with subsequent sampling times at 13:00, 16:00, 19:00, 22:00 and at 01:00, 04:00 07:00h on Friday. Melatonin concentration (MC) was measured by commercials ELISA kit tests.